Evidence for an integrated healthcare and psychosocial multidisciplinary model to address rough sleeping. (26th August 2019) - Parsell, Cameron; Clarke, Andrew; Vorsina, Margarita
Abstract: People who sleep rough/experience unsheltered homelessness face barriers accessing mainstream healthcare and psychosocial services. The barriers to service access exacerbate poor health, which in turn create additional challenges for rough sleepers to access health and psychosocial services, including stable housing. The study presents descriptive statistics to identify housing outcomes of people working with a Multidisciplinary Model that comprises integrated healthcare and psychosocial support, and qualitative data with clients and service providers to investigate how the Model is experienced and delivered in practice. Fieldwork was conducted between December 2016 and March 2018 with the Multidisciplinary Team operating in Cairns, in the far north of Australia. Qualitative data are drawn from in‐depth interviews with 26 rough sleepers and 33 health and psychosocial service providers from the Multidisciplinary Team and the wider service system. Descriptive statistics show that 67% of clients who were sleeping rough were supported to immediately access stable housing, and at the end of the program, all clients remained housed. The qualitative findings illustrated how integrated healthcare and psychosocial outreach enabled people sleeping rough to overcome barriers they experienced accessing mainstream healthcare and other services. With the benefit of healthcare, people felt sufficiently well to engage with the psychosocial service providers to have their housing and other psychosocial needs addressed. This article demonstrates how individual responsibility for and control over healthcare is not only a matter of the individual, but also a matter requiring systems change and the active provision of resources to cater for the constraints and opportunities present in people's immediate environments.